Entertainment industry Economics a guide for financial analysis - Vogel, Harold L. (Cambridge University Press, 2010)
"The entertainment industry is one of the largest sectors of the U.S. economy and is in fact becoming one of most prominent globally as well, in movies, music, television programming, advertising, broadcasting, cable, casino gambling and wagering, publishing performing arts, sports, theme parks, and toys and games. The eighth edition of Entertainment Industry Economics differs from its predecessors by inclusion of a new section on the legal aspects and limitations common to all such "experience" industries, reference to the emerging field of the psychology of entertainment, partial restructuring and expansion of the music chapter, enhancement of the section on advertising, and broadening of the coverage in the gaming and wagering chapter. The result is a comprehensive, up-to-date reference guide on the economics, financing, production, and marketing of entertainment in the United States and overseas. Investors, business executives, accountants, lawyers, arts administrators, and general readers will find that this book offers an invaluable guide to how entertainment industries operate" -- Provided by publisher